Phylogeography and invasion history of Aedes aegypti, the Dengue and Zika mosquito vector in Cape Verde islands (West Africa). (3rd August 2019) - Salgueiro, Patrícia; Serrano, Célia; Gomes, Bruno; Alves, Joana; Sousa, Carla A.; Abecasis, Ana; Pinto, João
Abstract: Aedes ‐borne arboviruses have spread globally with outbreaks of vast impact on human populations and health systems. The West African archipelago of Cape Verde had its first outbreak of Dengue in 2009, at the time the largest recorded in Africa, and was one of the few African countries affected by the Zika virus epidemic. Aedes aegypti was the mosquito vector involved in both outbreaks. We performed a phylogeographic and population genetics study of A. aegypti in Cape Verde in order to infer the geographic origin and evolutionary history of this mosquito. These results are discussed with respect to the implications for vector control and prevention of future outbreaks. Mosquitoes captured before and after the Dengue outbreak on the islands of Santiago, Brava, and Fogo were analyzed with two mitochondrial genes COI and ND4, 14 microsatellite loci and five kdr mutations. Genetic variability was comparable to other African populations. Our results suggest that A. aegypti invaded Cape Verde at the beginning of the Holocene from West Africa. Given the historic importance of Cape Verde in the transatlantic trade of the 16th–17th centuries, a possible contribution to the genetic pool of the founding populations in the New World cannot be fully discarded. However, contemporary gene flow with the Americas is likely to be infrequent. No kdr mutations associated with pyrethroid resistance were detected. The implications for vector control and prevention of future outbreaks are discussed.